Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A)3.5n.52+4.5n:53=19.9765625
5n(3.52+4:53)=185546875
5n.\(\frac{12}{5}\)=185546875
b)11.6x-1+2.6x+1=11.611+2.613
11.6x-1+2.6x+1 = 11. 612-1+ 2. 612+1
=> x= 12
c) 24-x / 165 = 326
24-x / 220= 230
24-x = 250
=> 4-x = 50
x= -46
c) \(\frac{2^{4-x}}{\left(2^4\right)^5}=\left(2^5\right)^6\)
\(2^{4-x}:2^{20}=\left(2^5\right)^6\)
\(2^{4-x}=2^{30}.2^{20}\)
\(2^{4-x}=2^{50}\)
=> \(4-x=50\)
=> \(x=4-50=-46\)
vậy x = -46
b) \(11\cdot6^{x-1}+2\cdot6^{x+1}=11\cdot6^{11}+2\cdot6^{13}\)
\(\Leftrightarrow11\cdot6^{x-1}+2\cdot6^{x+1}=11\cdot6^{12-1}+2\cdot6^{12+1}\)
\(\Leftrightarrow x=12\)
a: \(\Leftrightarrow3\cdot5^n\cdot25+4\cdot5^n\cdot\dfrac{1}{125}=19\cdot5^{10}\)
\(\Leftrightarrow5^n\cdot\left(75+\dfrac{4}{125}\right)=19\cdot5^{10}\)
\(\Leftrightarrow5^n\simeq2472903,228\)(vô lý)
b: \(\Leftrightarrow6^x\cdot11\cdot\dfrac{1}{6}+2\cdot6^x\cdot6=11\cdot6^{11}+2\cdot6^{11}\cdot36\)
\(\Leftrightarrow6^x\left(\dfrac{11}{6}+12\right)=6^{11}\cdot83\)
\(\Leftrightarrow6^x=6^{12}\)
hay x=12
Bài 1 :
a/ \(a^3.a^9=a^{3+9}=a^{12}\)
b/\(\left(a^5\right)^7=a^{5.7}=a^{35}\)
c/ \(\left(a^6\right).4.a^{12}=a^{24}.a^{12}.4=a^{24+12}.4=a^{36}.4\)
d/ \(\left(2^3\right)^5.\left(2^3\right)^3=2^{15}.2^9=2^{15+9}=2^{24}\)
e/ \(5^6:5^3+3^3.3^2\)
\(=5^3+3^5=125+243=368\)
i/ \(4.5^2-2.3^2\)
\(=2^2.5^2-2.3^2\)
\(=2^2.25-2^2.14\)
\(=2^2.\left(25-14\right)\)
\(=2^2.11\)
\(=4.11=44\)
Câu a )
S = 5 + 52 +..... + 52012
=> S \(⋮5\)
S = 5 + 52 +..... + 52012
S = ( 5 + 53 ) + ( 52 + 54 ) + ........ + ( 52010 + 52012 )
S = 5 ( 1 + 52 ) + 52 ( 1 + 52 ) + ......... + 52010 ( 1 + 52 )
S = 5 x 26 + 52 x 26 + ................ + 52010 x 26
S = 26 ( 5 + 52 + .... + 52010 )
=> S\(⋮26\)
=>\(S⋮13\)( do 26 = 13 x 2 )
Do ( 5 , 13 ) = 1
=> \(S⋮5x13\)
=> \(S⋮65\)
Bạn ơi : -9^0 hay là 9*0 vậy
Đáp án:
x = 41884188
Giải thích các bước giải:
103 - 57 : [-2 . (2x - 1) . 2 - (-9) . 0] = -106
→ 103 - 57 : [-2 . (2x - 1) . 2] = -106
→ 103 - 57 : [-4 . (2x - 1)] = -106
→ 103 - 57 : (-8x + 4) = -106
→ 57 : (-8x + 4) = 103 - (-106)
→ 57 : (-8x + 4) = 103 + 106
→ 57 : (-8x + 4) = 209
→ -8x + 4 = 311311
→ -8x = −4111−4111
→ x = 41884188
Vậy x = 4188
Đáp án:
x = 41884188
Giải thích các bước giải:
103 - 57 : [-2 . (2x - 1) . 2 - (-9) . 0] = -106
→ 103 - 57 : [-2 . (2x - 1) . 2] = -106
→ 103 - 57 : [-4 . (2x - 1)] = -106
→ 103 - 57 : (-8x + 4) = -106
→ 57 : (-8x + 4) = 103 - (-106)
→ 57 : (-8x + 4) = 103 + 106
→ 57 : (-8x + 4) = 209
→ -8x + 4 = 3/11
→ -8x = −41/11
→ x = 41/88
Vậy x = 41/88